Five directors auteurism from Assayas to Ozon - Ince, Kate 1963- (French film directors, 2008)
Auteurism – the idea that a director of a film is its source of meaning and should retain creative control over the finished product – has been one of film studies’ most important paradigms ever since the French New Wave of the late 1950s and early 1960s, and the adoption of the term auteur by Andrew Sarris.Through the popular, controversial and critically acclaimed films of Olivier Assayas, Jacques Audiard, the Dardenne borthers, Michael Haneke and Francois Ozon, this book looks into how the meaning of ‘auteur’ has changed over this half-century, and assesses the current state of Francophone auteur cinema. It combines French philosophical and sociological approaches with methodologies from the Anglo-American fields of gender studies, queer theory and postmodernism.This volume will be of interest to researchers and students of film studies, European cinema and French and Francophone studies, as well as to film enthusiasts